2022
DOI: 10.12688/wellcomeopenres.17041.2
|View full text |Cite
|
Sign up to set email alerts
|

Bias from questionnaire invitation and response in COVID-19 research: an example using ALSPAC

Abstract: Background: Longitudinal studies are crucial for identifying potential risk factors for infection with, and consequences of, COVID-19, but relationships can be biased if they are associated with invitation and response to data collection. We describe factors relating to questionnaire invitation and response in COVID-19 questionnaire data collection in a multigenerational birth cohort (the Avon Longitudinal Study of Parents and Children, ALSPAC). Methods: We analysed online questionnaires completed between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…This may cause collider bias and affect findings as outlined elsewhere ( Griffith et al, 2020 ; Munafò et al, 2018 ). For example, indicators of poorer health have been associated with lower response to COVID-19 questionnaires in ALSPAC ( Fernández-Sanlés et al, 2021 ), which may bias the observed results. Acknowledging the potential effects of biases, the replication of multiple associations with lower antibody levels across compositionally varied TwinsUK and ALSPAC cohorts and across multiple rounds of vaccination support the robustness of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…This may cause collider bias and affect findings as outlined elsewhere ( Griffith et al, 2020 ; Munafò et al, 2018 ). For example, indicators of poorer health have been associated with lower response to COVID-19 questionnaires in ALSPAC ( Fernández-Sanlés et al, 2021 ), which may bias the observed results. Acknowledging the potential effects of biases, the replication of multiple associations with lower antibody levels across compositionally varied TwinsUK and ALSPAC cohorts and across multiple rounds of vaccination support the robustness of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study is very novel as it is the first study assessing the effects of active workstation on lipoprotein subfraction profile in healthy sedentary workers. The limited small sample size was partly due to recruitment difficulties linked with the Covid-19 pandemic when the study was conducted, which may be another source of bias [61,62]. Nevertheless, the study was a randomized controlled trial, precluding recruitment bias as well as the bias related with external factors.…”
Section: Limitationsmentioning
confidence: 99%
“…When the exposure and outcome (or a cause of these) influence the probability of being selected into the analytical sample, collider bias can be introduced 16. In the context of covid-19, selection bias can arise from differential response to covid-19 study questionnaires, differential risk of being exposed to SARS-Cov-2 infection, and differences in who receives a SARS-CoV-2 test or who is admitted to hospital 1415. For example, if a person never receives a SARS-CoV-2 test, their covid-19 status remains unknown, and they would not be selected into any analysis that depends on having a test (table 1).…”
Section: Selection Biasmentioning
confidence: 99%
“… 16 In the context of covid-19, selection bias can arise from differential response to covid-19 study questionnaires, differential risk of being exposed to SARS-Cov-2 infection, and differences in who receives a SARS-CoV-2 test or who is admitted to hospital. 14 15 For example, if a person never receives a SARS-CoV-2 test, their covid-19 status remains unknown, and they would not be selected into any analysis that depends on having a test ( table 1 ). Genome wide association studies (GWAS) are studies where genetic variants are tested for an association with a phenotype (ie, a trait or disease outcome, such as body mass index (BMI)).…”
Section: Selection Biasmentioning
confidence: 99%
See 1 more Smart Citation